LEADERSHIP DEVELOPMENT STRATEGIES in IMPROVING PRINCIPALS PERFORMANCE in PUBLIC PRIMARY SCHOOLS of TIGRAY REGIONAL STATE, ETHIOPIA. - Nigusse, Gebreegziabher Meles; Tsegai, Mulugeta; Seyoum, Yilfashewa; Hundessa, Feyera Dinsa (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
The purpose of the study was to investigate how leadership development strategies enhance principals' performance in public primary schools of Tigray Regional State. The study utilized mixed methods sequential explanatory research design. The primary data sources were teachers, school leaders, cluster supervisors, teacher development program and curriculum development and implementation performers, and coordinators. On the other hand, secondary sources such as plans and reports were reviewed. Samples were selected using simple random, stratified and purposive sampling techniques. Data were collected through a questionnaire, an interview and document analysis. Thematic analysis was used to analyze qualitative data, and quantitative data were analyzed using descriptive statistics and independent samples t-test. The findings of the study revealed that, the current leadership development has moderately impacted principals' efficacy. The study highlighted lack of comprehensive training needs analysis; absence of technical support; the missing links between principal’s needs and contents of the training; and lack of awareness on the side of stakeholders as hindering factors negatively impacting the effectiveness of LD strategies and leading to resource inefficiency and participant dissatisfaction. Therefore, it is recommended that the Regional Education Bureau and the Woreda Education Offices should conduct training needs analysis on principal’s trainings, targeting at identifying the natures of the previous trainings; experience of the training participants, the skill gaps, and training needs; to make the training programs need based and attract interested participants.